Analyzing the (mis)fit between the institutional and ecological networks of the Indo-West Pacific. (March 2015) - Treml, Eric A.; Fidelman, Pedro I.J.; Kininmonth, Stuart; Ekstrom, Julia A.; Bodin, Örjan
Highlights: We proposed an approach for evaluating ecological–institutional fit and alignment. We mapped cross-country institutional linkages related to marine management in the Indo-West Pacific. We identified geopolitical (mis)fit across the region's ecology and governance. The results may guide management of ecological processes spanning multiple jurisdictions. Abstract: Critical to improving environmental governance is understanding the fit (alignment) between institutional arrangements and key ecological processes. This is particularly true for biodiversity hotpots and ecologically sensitive areas that are subject to significant impacts from human activities. Here, we have developed an innovative approach to quantify ecological-institutional alignment across an environmentally and politically complex large-scale marine social-ecological system. We mapped the trans-boundary networks of marine population dispersal corridors, and intersected these with estimates of cross-country institutional linkages related to marine management and conservation. In integrating large-scale ecological-institutional networks, we identify geopolitical fit and misfit between a region's ecological processes and its governance. We have demonstrated this approach in the Indo-West Pacific region, a global marine biodiversity hotpot in the Indo-West Pacific. We present region-specific institutional and ecological networks, highlight current challenges, and suggest future directions to refine the proposed approach to quantify alignment between ecological processes and governance arrangements. Ultimately, our method has the potential to assist management efforts in prioritizing and strengthening governance to effectively safeguard ecological processes across multiple jurisdictions.